Psychometric properties of public trust in Covid-19 control and prevention policies questionnaire - Riaz Alaei Kalajahi; Mohammad Saadati; Saber Azami Aghdash; Ramin Rezapour; Mehdi Nouri; Naser Derakhshani; Koustuv Dalal (BMC, 2022)
Highlights: Investigating public trust during the outbreak of Covid-19 is of utmost important for both research and policy making perspectives. COV-Trust tool (Seven factors and 31 items) was developed and validated. COV-Trust tool comprehensively assesses public trust in various aspects of policies and their determinants and can provide valuable information for promoting the effectiveness of policies.